A Conference of the Baltic Heritage Network in Rīga, Latvia. (2nd April 2016) - Jacobs, David
ABSTRACT: The article summarizes the fourth conference of the Baltic Heritage Network, held in Rīga, Latvia on June 30–July 2, 2015.